1990
DOI: 10.1007/bf00198792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high light on the efficiency of photochemical energy conversion in a variety of lichen species with green and blue-green phycobionts

Abstract: Exposure to high light induced a quantitatively similar decrease in the rate of photosynthesis at limiting photon flux density (PFD) and of photosystem II (PSII) photochemical efficiency, FV/FM, in both green and blue-green algal lichens which were fully hydrated. Such depressions in the efficiency of photochemical energy conversion were generally reversible in green algal lichens but rather sustained in blue-green algal lichens. This greater susceptibility of blue-green algal lichens to sustained photoinhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 29 publications
(24 reference statements)
9
72
1
Order By: Relevance
“…Cryptobiotical crusts derived from Tanzania showed an unusually high Fv/Fm fluorescence value, approximately 0.8, after 80 min of rehydration. This value corresponded to the observation in healthy leaves of higher plants that is about 0.8 [47] and higher than the highest value observed in cyanobacterial lichens, 0.62 [48]. However, the crusts did not contain just cyanobacteria but green algae also, which might explain the values of variable fluorescence.…”
Section: Chlorophyll-a Fluorescence Responsessupporting
confidence: 82%
See 1 more Smart Citation
“…Cryptobiotical crusts derived from Tanzania showed an unusually high Fv/Fm fluorescence value, approximately 0.8, after 80 min of rehydration. This value corresponded to the observation in healthy leaves of higher plants that is about 0.8 [47] and higher than the highest value observed in cyanobacterial lichens, 0.62 [48]. However, the crusts did not contain just cyanobacteria but green algae also, which might explain the values of variable fluorescence.…”
Section: Chlorophyll-a Fluorescence Responsessupporting
confidence: 82%
“…Longterm rehydration (3 hours) resulted in lower and steadystate values of Fv/Fm, between 0.4 and 0.6 compared with 10 min of rehydration due to the complete recovery of photosynthetic system ( Figure 6). Many studies observed similar results for cyanobacteria that reflect a steady-state condition of photochemistry [21,48]. The relatively high qP, even at high light intensities, is related to the ability of cyanobacteria to remove electrons from PSII and maintain the centres open [21,49].…”
Section: Chlorophyll-a Fluorescence Responsesmentioning
confidence: 72%
“…11). In contrast, cyanobacteria grown under artificial laboratory conditions sustained damage to the photosynthetic apparatus and did not recover for several days after sudden transfer to high light (Demmig-Adams et al, 1990b). Survival in the extremely high-light habitat of the inselbergs, therefore, requires other mechanisms to protect U.…”
Section: Discussionmentioning
confidence: 97%
“…The equipment was identical to that of Lange et al (1993) and similar to that of Lange et al (1990). Three different instruments were used to measure lichen photosynthesis and dark respiration.…”
Section: Exchange Measurementsmentioning
confidence: 99%